2022
DOI: 10.2147/idr.s358248
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CRISPR-Cas Systems and Their Possible Association with Antibiotic Resistance in Enterococcus faecalis and Enterococcus faecium Collected from Hospital Wastewater

Abstract: Purpose This study aimed to evaluate the presence of CRISPR-Cas system genes and their possible association with antibiotic resistance patterns of Enterococcus faecalis and Enterococcus faecium species isolated from hospital wastewater (HWW) samples of several hospitals. Methods HWW samples (200 mL) were collected from wastewater discharged from different hospitals from October 2020 to March 2021. The isolation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
2
23
1
Order By: Relevance
“…In the current study, we found that the presence of orphan CRISPR2(42%) was more in Enterococcus than CRISPR1-Cas (23%) and CRISPR3-Cas (5%), which was similar to Alduhaidhawi. 28 In non-clinical Enterococcus faecium isolates, Huescas et al 29 demonstrated a higher prevalence rate of CRISPR2 and lower frequency of CRISPR1-Cas (5.6%) and CRISPR3-Cas (1.8%) system. In contrast to our study, Palmer et al 30 found that CRISPR2 was present in all Enterococcus faecalis isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that the presence of orphan CRISPR2(42%) was more in Enterococcus than CRISPR1-Cas (23%) and CRISPR3-Cas (5%), which was similar to Alduhaidhawi. 28 In non-clinical Enterococcus faecium isolates, Huescas et al 29 demonstrated a higher prevalence rate of CRISPR2 and lower frequency of CRISPR1-Cas (5.6%) and CRISPR3-Cas (1.8%) system. In contrast to our study, Palmer et al 30 found that CRISPR2 was present in all Enterococcus faecalis isolates.…”
Section: Discussionmentioning
confidence: 99%
“… 59 The literature suggested an inverse relationship between the occurrence of the type II CRISPR-Cas system and antibiotic resistance in E. faecalis . 107 E. faecalis isolates generally possess only the orphan CRISPR2. 108 Most multidrug-resistant E. faecalis strains generally lack the functional CRISPR1-Cas or CRISPR3-Cas systems.…”
Section: Crispr-cas System’s Role In the Development Of Antibiotic Re...mentioning
confidence: 99%
“…A study [ 119 ] has shown that multidrug-resistant enterococci lack CRISPR/Cas system elements, suggesting that the CRISPR/Cas system in bacteria may play an important role in hindering drug resistance transmission. The literature suggests an inverse relationship between the occurrence of the type II CRISPR-Cas system and antibiotic resistance in Enterococcus faecalis [ 120 ].…”
Section: Factors Influencing the Transfer Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…e literature suggests an inverse relationship between the occurrence of the type II CRISPR-Cas system and antibiotic resistance in Enterococcus faecalis [120].…”
Section: Crispr-cas (Clustered Regularly Interspaced Short Palindromi...mentioning
confidence: 99%